2009
DOI: 10.1017/s1743921310006988
|View full text |Cite
|
Sign up to set email alerts
|

Growing Supermassive Black Holes in Cosmological Simulations of Structure Formation

Abstract: Abstract. We discuss a numerical model for black hole (BH) growth and feedback that allows simultaneous tracking of the evolution of galaxies and their central BHs in fully cosmological simulations. After describing the main features of the numerical model adopted, we show how BHs in these simulations affect the properties of their host halos and how this in turn impacts the growth of the BHs themselves. We also present results from a set of simulations specifically designed to address the issue of BH assembly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Similar, seemingly bizarre, 'wandering' behaviour for massive luminous objects has recently been found by au-thors in different branches of Astrophysics. The displacement of luminous super-massive black holes from the centre of a young gas-rich galaxy was found by Sijacki et al (2010) in their simulations of merging super-massive black holes displaced from the galactic centre due to gravitational kicks. They found that luminous black holes were ejected further than expected given their kick and did not come back to the galaxy centre afterwards.…”
Section: Dynamics Of the Luminous Corementioning
confidence: 94%
See 1 more Smart Citation
“…Similar, seemingly bizarre, 'wandering' behaviour for massive luminous objects has recently been found by au-thors in different branches of Astrophysics. The displacement of luminous super-massive black holes from the centre of a young gas-rich galaxy was found by Sijacki et al (2010) in their simulations of merging super-massive black holes displaced from the galactic centre due to gravitational kicks. They found that luminous black holes were ejected further than expected given their kick and did not come back to the galaxy centre afterwards.…”
Section: Dynamics Of the Luminous Corementioning
confidence: 94%
“…Black holes of zero luminosity, on the other hand, returned to the galaxy centre in agreement with classical dynamical friction theory. Sijacki et al (2010) identified the asymmetry in the gas distribution around the SMBH as the driver of this unexpected behavior. In Chandrasekhar dynamical friction, there is a higher density trail behind the massive perturber.…”
Section: Dynamics Of the Luminous Corementioning
confidence: 99%